Transcriptional Profiling Reveals the Regulatory Role of DNER in Promoting Pancreatic Neuroendocrine Neoplasms - He, Rui; Zhang, Wunai; Chen, Shuo; Liu, Yang; Yang, Wenbin; Li, Junhui (Frontiers in Genetics, 2020)
Wnt/β-catenin and NOTCH signaling contribute to the pathogenesis and growth of pancreatic neuroendocrine neoplasms (PanNENs). The wnt and Notch signaling pathways form an integrated signaling device termed ‘wntch’ and regulate stochastic cell fate decisions, suggesting the essentiality of Wnt/Notch interactions in disease progression. However, the function of Wnt/Notch interactions in PanNENs is unclear. We analyzed RNA sequencing (RNA-seq) data to identify differentially expressed lncRNAs, mRNAs and pathways according to enriched Gene Ontology (GO) terms and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways associated with PanNENs. RNA-seq analysis revealed that the levels of the lncRNA XLOC_221242 and the mRNA encoding Delta/Notch-like epidermal growth factor (EGF)-related receptor (DNER) were significantly increased in tumor tissues compared with normal tissues (n = 3). Protein-protein interaction (PPI) prediction combined with transcriptional profiling data analysis revealed that DNER expression levels were positively correlated with those of DNA-binding factor (RBPJ), S phase kinase-associated protein 1 (Skp1), CTNNB1 and Cadherin-2 (CDH2), which promote PanNEN tumorigenesis and progression. These results were consistent with those of immunohistochemical analysis of DNER, RBPJ, SKP1, CTNNB1 and CDH2 expression (n = 15). These findings provide compelling clinical and molecular evidence supporting the conclusion that DNER and the related RBPJ, SKP1, CTNNB1 and CDH2 signaling contribute to PanNEN tumorigenesis and progression by activating wnt/Notch interactions.